On Weak Forms of Open and Closed Functions Between Bitopological Spaces (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of open and closed functions defined between bitopological spaces, called weakly $θ(τ_1,τ_2)b$-open functions and weakly $θ(τ_1,τ_2)b$-closed functions. Moreover, several characterizations and some properties concerning weakly $θ(τ_1,τ_2)b$-open functions and weakly $θ(τ_1,τ_2)b$-closed functions are established.
Keywords: weakly $θ(τ_1,τ_2)b$-open function; weakly $θ(τ_1,τ_2)b$-closed function